Fibrinogen Binding to ICAM-1 on EA.hy 926 Endothelial Cells Is Dependent on an Intact Cytoskeleton - van de Stolpe, Anja; Jacobs, Nancy; Hage, Willem J; Tertoolen, Leon; van Kooyk, Yvette; Nováková, Irena RO; de Witte, Theo (Thrombosis and Haemostasis, 1996)
Fibrinogen is a ligand for Intercellular Adhesion Molecule-1 (ICAM-1), and enhances monocyte-endothelial cell interaction by coupling Mac-1 on monocytes to ICAM-1 on endothelial cells. We investigated the role of the cytoskeleton in fibrinogen binding to the human endothelial cell line EA.hy 926 using immunofluorescence techniques. In this cell line TNFα induced the simultaneous appearance of stress fibers and of ICAM-1, which was clustered predominantly on endothelial cell projections. Incubation of TNFα-stimulated endothelial cells with fibrinogen resulted in binding of fibrinogen to ICAM-1 on these cell projections. Disruption of the cytoskeleton by cytocholasin B abolished fibrinogen binding. Activation of protein kinase C with 12-O-tetradecanoyl phorbol- 13-acetate resulted in simultaneous loss of both stress fibers and fibrinogen binding. These results suggest that a connection between ICAM-1 and the cytoskeleton results in clustering of ICAM-1 on cell projections, which is required for fibrinogen binding.